2021
DOI: 10.1097/adm.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Children's Problematic Internet-related Behaviors and Psychological Distress During the Onset of the COVID-19 Pandemic: A Longitudinal Study

Abstract: Background: The outbreak of the coronavirus disease 2019 (COVID-19) pandemic has generated negative effects on psychological wellbeing worldwide, including in schoolchildren. Government requirements to stay at home and avoid social and school settings may impact psychological well-being by modifying various behaviors such as problematic phone and Internet use, yet there is a paucity of research on this issue. This study examined whether the COVID-19 outbreak may have impacted problematic smartphone use (PSU), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 49 publications
(114 reference statements)
2
66
1
1
Order By: Relevance
“…The 0-10 Visual Analogue Scale (VAS) was used to assess the worry concerning COVID-19 infection among the schoolchildren. Although there are criticisms regarding the use of a single item instead of using multiple items to capture an underlying concept (Fisher, Matthews, & Gibbons, 2016), the use of the single VAS item to assess the worry was recently validated in prior research on schoolchildren (Chen, Chen, Hou, et al, 2021). More specifically, the general consensus is that using multiple items to assess an underlying concept can have better psychometric properties than using a single item.…”
Section: Problematic Gaming (Pg) the Internet Gaming Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…The 0-10 Visual Analogue Scale (VAS) was used to assess the worry concerning COVID-19 infection among the schoolchildren. Although there are criticisms regarding the use of a single item instead of using multiple items to capture an underlying concept (Fisher, Matthews, & Gibbons, 2016), the use of the single VAS item to assess the worry was recently validated in prior research on schoolchildren (Chen, Chen, Hou, et al, 2021). More specifically, the general consensus is that using multiple items to assess an underlying concept can have better psychometric properties than using a single item.…”
Section: Problematic Gaming (Pg) the Internet Gaming Disordermentioning
confidence: 99%
“…It also examined the associations between changes in problematic internet use across the three pandemic stages and COVID-19-related psychological distress during the COVID-19 recovery stage among schoolchildren. According to prior evidence regarding positive associations between problematic internet use and psychological distress Chen, Chen, Hou, et al, 2021;, the present study hypothesized that (i) the group with higher level of problematic internet use would have greater psychological distress across different stages of COVID-19 pandemic; and (ii) changes of problematic internet use would be associated with COVID-19-related psychological distress. Aside from the hypotheses, the present study explored the trajectory of PSU, PSMU, and PG across three stages of COVID-19 outbreak (i.e., before the COVID-19 outbreak, during the outbreak, and during recovery) given that there is no relevant evidence currently.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…PSU and PSMU among children have been of concern to clinicians and policy makers because of their purported association with children's psychological health, although the model of compensatory internet use suggests a continuum for smartphone and social media use (i.e., from non-problematic to problematic) (15). Indeed, several studies have suggested that PSU and PSMU are associated with greater depression, anxiety, and stress (16)(17)(18)(19)(20)(21). The social distancing and school suspensions due to COVID-19 could possibly lead to undesirable lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the publications (76%) indicated heightened anxiety during the pandemic. Among the 21 longitudinal studies, 16 reported higher levels of anxiety (Breaux et al, 2021;C. Y. Chen et al, 2021;Conti et al, 2020;Elmer et al, 2020;Evans et al, 2021;Hawes, Szenczy, Olino, et al, 2021;Huckins et al, 2020;Knowles & Olatunji, 2021;S.…”
Section: Youth Mental Health During Covid-19mentioning
confidence: 99%